Establishing the true causes of defects to ensure the quality of continuously cast billets and hot‑rolled products at all stages of the process chain at OJSC “BSW – Management Company of the Holding “BMC” - A. V. Tereshchenko; I. A. Kovaleva (Литьë и металлургия)
Establishing the true causes of defects is one of the main prerequisites for improving the quality of metal products. One of the undesirable phenomena in the production of continuously cast billets, hot‑rolled products is the oxidation of hot metal in the environment with the formation of scale on its surface. Defects, which are violations of the continuity of the metal and deviations from the normal specified macro‑and microstructure, signifi antly reduce the technological plasticity of the metal in the conditions of its processing and operational stability.After hot rolling of a circle of 95 mm steel grade 30MpV4, surface defects were found in the finishing line. To study and establish the nature of surface defects from hot‑rolled blanks, as well as continuously cast blanks, samples were taken.Analyzing metallographic studies of defects and the production technology of the studied steel grade 30MnB4, it was found that the defects were formed as a result of mechanical damage to the continuously cast billet in the area of the pulling‑correct unit. The reason for the formation of the defect is the ingress of scale on the guide rollers.